The redistributive power of cash transfers vs VAT exemptions: A multi-country study. (March 2022) - Warwick, Ross; Harris, Tom; Phillips, David; Goldman, Maya; Jellema, Jon; Inchauste, Gabriela; Goraus-Tańska, Karolina
Highlights: We use microsimulation models to study the effects of reduced VAT rates and exemptions on revenues, poverty and inequality. In isolation, reduced VAT rates and exemptions in six LMICs studied are poverty-reducing. They are often expensive in terms of foregone tax revenue, and in all cases richer households benefit the most in cash terms. Though better targeted at poor households, existing cash transfer programmes often miss large shares of poor households. Recycling the revenue yield from a broader VAT base with universal benefits would reduce inequality and most measures of poverty. Abstract: Like high-income countries, low- and middle-income countries (LMICs) offer reduced rates and exemptions on particular goods and services in their value-added tax (VAT) systems. These policies are often motivated by distributional concerns and target items thought to take up a larger share of the budgets of poorer households. This paper explores the effectiveness of such policies in six LMICs. We estimate their impact on tax revenues, inequality and poverty, and compare these effects to existing cash transfer schemes and a hypothetical Universal Transfer (UT) funded by broadening the VAT base. To do so, we use tax-benefit microsimulation models incorporating input–output tables, allowing us to estimate the impact of exemptions on consumer prices due to VAT embedded in supply chains. We show that although preferential VAT rates reduce poverty, they are not well targeted towards poor households overall. Existing cash transfer schemes are better targeted but generally have limited coverage. A UT funded by a broader VAT base would create large net gains for the poorest households, reducing inequality and most measures of extreme poverty in each of the countries studied. Our results suggest that the widespread practice of providing special VAT treatment to certain goods and services is an expensive way of reaching poor households. In principle, expanding the VAT base and social protection schemes in tandem has the potential to both raise tax revenues and reduce poverty. Such reforms therefore warrant consideration for LMICs as they pursue Domestic Revenue Mobilisation and broader development objectives.